Тhe investigation of X-rays irradiation effect on the mobility of dislocations in LiF crystals - Petchenko, О.M.; Petchenko, G.О.; Boiko, S.M. (Вопросы атомной науки и техники, 2018)
An acoustic pulse echo method at a frequency of 7.5 MHz was used to study the dependence of the absorption α
and the relative velocity of ultrasound Δv/v₀
in single crystals of LiF with a residual deformation of ε = 0.65%, at
300 K in the irradiation dose range 0...1057 R. It was found that an increase in the irradiation dose leads to a noticeable decrease in the damping and the relative ultrasound velocity in the sample as a result of a decrease in the effective density of the dislocation segment L when it is fixed by radiation centers. Based on the results of measurements
of acoustic characteristics, the absolute value of the damping factor of dislocations B is determined and compared
with the literature data obtained from the high-frequency branch of dislocation resonance. Акустичним імпульсним ехо-методом на частоті 7,5 МГц досліджено залежності поглинання α і відносної швидкості ультразвуку
Δv/v₀ у монокристалах LiF із залишковою деформацією ε = 0,65% при 300 К в
інтервалі доз опромінення 0…1057 P. Виявлено, що збільшення дози опромінення призводить до помітного
зниження згасання і відносної швидкості ультразвуку в зразку через зменшення ефективної довжини дислокаційного сегмента L при його закріпленні радіаційними центрами. На основі результатів вимірювань акустичних характеристик визначено абсолютне значення величини коефіцієнта демпфування дислокацій В і
проведено його порівняння з літературними даними, одержаними за високочастотною гілкою дислокаційного резонансу. Акустическим импульсным эхо-методом на частоте 7,5 МГц исследованы зависимости поглощения α и относительной скорости ультразвука Δv/v₀ в монокристаллах LiF с остаточной деформацией ε = 0,65% при 300 К в интервале доз облучения 0…1057 P. Обнаружено, что увеличение дозы облучения приводит к заметному снижению затухания и относительной скорости ультразвука в образце вследствие уменьшения эффективной длины дислокационного сегмента L при его закреплении радиационными центрами. На основе
результатов измерений акустических характеристик определено абсолютное значение величины коэффициента демпфирования дислокаций В и проведено его сравнение с литературными данными, полученными по
высокочастотной ветви дислокационного резонанса.